Inadvertent temporary pacemaker lead placement in aortic sinus - Naveen Garg; Nagaraja Moorthy (Heart Views, 2013)
Inadvertent placement of pacing leads into abnormal locations is potentially very dangerous. However, in emergency situations and without fluoroscopic guidance, these complications do occur. We report a case of an elderly male who underwent temporary pacemaker lead implantation without fluoroscopic guidance for cardiac arrest, but later the pacemaker lead was found to be in the non-coronary aortic sinus, but still capturing the myocardium. Interestingly, the post-pacing electrocardiography was mimicking atrial pacing.